Isolated local recurrence or solitary solid organ metastasis after esophagectomy for cancer is not the end of the road. Issue 1 (21st December 2016) - Depypere, L.; Lerut, T.; Moons, J.; Coosemans, W.; Decker, G.; Van Veer, H.; De Leyn, P.; Nafteux, P.
SUMMARY: Recurrent disease after esophagectomy bears an infaust prognosis, especially when multiple recurrences are present. But little is known about survival in patients with limited recurrence (solitary locoregional recurrence or solid organ metastasis). Herein, we report our experience with these subgroups. We analyzed 1754 consecutive patients surgically treated with curative resection for esophageal cancer and cancer of the gastroesophageal junction between 1990 and 2012. Seven subgroups were defined according to the recurrence type (locoregional vs. organ metastasis), the site of recurrence (abdominal, thoracic, cervical for lymph nodes and lung, liver, adrenals and others for organ metastasis) and also the number of lesions (one vs. multiple lymph node stations or organ metastasis) Of these groups; clinical isolated locoregional recurrence (ciLR) was defined as solitary lymph-node recurrence confined to one compartment (cervical, thoracic or abdominal, within or outside surgical dissection-field) at clinical staging. Clinical solitary solid organ metastasis (csSOM) was defined as metastasis in a resectable solid organ, i.e. liver, lung, brain or adrenal. Salvage therapies were grouped in five categories. Kaplan–Meier curves were used to calculate survival. Recurrent disease was observed in 766 patients (43.7%) with overall 5-year survival of 4.5% after diagnosis of recurrence. Fifty-seven patients (7.4%) showed ciLR and 110 (14.4%) csSOM. Median time-to-recurrence was 16.8 months in ciLR and 9.9 months in csSOM ( P  = 0.0074). Survival is significantly improved compared to supportive therapy when local therapy is possible ( P  < 0.0001). In 25 (15%) of ciLR or csSOM patients, surgical therapy with or without systemic therapy, yielded a 5-year survival of 49.9% (median 54.8 months) after diagnosis of recurrence. When surgery was impossible or contraindicated, the combination of chemoradiotherapy appeared to be superior to chemotherapy alone (respectively 27.0% vs. 4.6% 5-year survival) or radiotherapy alone (no 5-year survival). Recurrent disease after esophagectomy is a common problem with poor overall survival. However prolonged survival could be obtained in selected patients if the recurrent disease is limited to ciLR or csSOM, if surgery (+/- systemic therapy) can be performed. If not a combination of chemoradiotherapy seems to offer the second best option. Patients presenting with a ciLR or csSOM should be discussed in a dedicated multidisciplinary team meeting as to evaluate and define the place of salvage treatment which in well selected cases could offer a perspective of prolonged survival.